Pengembangan Media KOMPAS (Komik IPA SD) Pada Materi Perubahan Wujud Benda Untuk Meningkatkan Minat Belajar Siswa Kelas 3 Sekolah Dasar - Meika Ferania; Krisma Widi Wardani (Peneliti.net, 2022)
Based on the results of observations, there are problems in elementary school students, namely the lack of interest in learning students in learning science using textbooks. T he purpose of this research and development is to develop media KOMPAS (Komik IPA SD) which can increase students' interest in learning. Media KOMPAS (Komik IPA SD) was made using the Sukmadinata development model with the ADDIE development stage. The steps used in this research and development are; (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. Based on the results of the study, media KOMPAS (Komik IPA SD) obtained a score with very good criteria, so it was feasible to be used as a learning medium. The average obtained from media experts is 90% with very high or very good assessment criteria and the average obtained from material experts is 85% with very good assessment criteria. The results of the implementation of media KOMPAS (Komik IPA SD) conducted on teachers got a good score of 93% and the response of 24 students in the class to media KOMPAS (Komik IPA SD) got a result of 88.6% with very good assessment criteria. In this way, media KOMPAS (Komik IPA SD) is able to increase students' interest in learning.